Art as an alternative resource for reintegration and Rehabilitation Opportunities of Inmate Population in the prison system - Vladimir Carbajal, Roberto (2017)
This article discusses the incorporation of Art as part of a comprehensive plan for the rehabilitation and reintegration of the prisoner as if we see the artistic event as an opportunity to develop sensitivity and other cognitive processes in order to contribute to the inmate population to restore confidence, integrity and psychically set free from a state of tension and frustration. One action plan could be developed from the stage of confidence to adapt well to understand this process as part of a whole arises involving a national policy on rehabilitation and reintegration of hand with other sectors that may be involved such as the company private institutions of higher education, art schools and others that join efforts to have a more lenient future society.